ORGANIZATIONAL CONDITIONS AT THE ENTERPRISE LEVEL FOR THE IMPLEMENTATION OF COMPLEX ECONOMIC ANALYSIS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The article extensively covers the organizational conditions necessary for the formation of a comprehensive economic analysis system at the enterprise level and its effective implementation. The increasing importance of analytical activities in achieving strategic goals and objectives facing enterprises in a market economy is substantiated. The article also develops practical recommendations for improving analytical processes.
Keywords: enterprise; complex economic analysis; analysis; organizational conditions; information system; digital economy; management decisions